Biosorption of aquatic Pb2+, Hg2+, and Cd2+ using a combined biosorbent—Aspergillus niger-Treated Rice Straw. Issue 4 (4th March 2018) - Cui, Han; Li, Fangyuan; Ren, Binqiao; Xue, Chao; Cui, Chongwei; Wang, Jing-Yao
ABSTRACT: The biosorbent used for removal of Pb 2+, Hg 2+, and Cd 2+ from aqueous solutions was rice straw fermented by Aspergillus niger (ARS), and raw rice straw (RRS) was used as a control. When inoculum size, material–water ratio, and temperature were 10 6, 100%, and 303K, respectively, the optimized spore number was 10 9 . The ARS exhibited a lager pore biosorption, which was better than RRS. The biosorption mechanism was involved in chelation with functional groups such as C-H, C = O, C-O, and C = C, and the biosorption data obtained were well described by the pseudo-second-order kinetic equation and the Freundlich isotherm model. GRAPHICAL ABSTRACT: